Pengaruh Media Manipulatif Terhadap Kemampuan Mengenal Konsep Bilangan pada Anak Usia 4-5 Tahun di PAUD Zayyan Palembang - Aryanti, Tika; Lian, Bukman; Novianti, Rahman (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine whether the effect of using manipulative media on increasing the ability to recognize the concept of numbers in children aged 4-5 years at PAUD Zayyan Palembang. The research method used in this research is qualitative research, the type of research used is true experimental design. The research population was all children of PAUD Zayyan Palembang in class A2. The sampling technique used a random sampling of the selected samples, namely class A2 which was used as the experimental class and A1 as the control class. Methods of data collection using observation and documentation. Based on the calculations obtained for the pretest data, the normality test of the data obtained is 40.61 and the posttest data is 83.53, so it can be said from the two data that the distribution is normal. Then the results of the calculation of the data normality test for t_(count )<t_table or 1.09 < 2.160. The next stage is testing the hypothesis from the results of the t-test calculation obtained t_count = 4.55 and t_table = 1.78. Thus it can be concluded that t_(count )> t_table or 4.55 > 1.78, meaning Ho is rejected and Ha is accepted, then the comparison of pretest data and posttest data can be stated that manipulative media has a significant influence on the ability to recognize the concept of numbers in children aged 4-5 years at PAUD Zayyan Palembang.